Evaluating the maturity level of public service agency at Jambi University: Analysis and recommendations for enhancing public services - Junaidi, Junaidi; Yusrizal, Yusrizal; Marzal, Jefri; Jumaili, Salman (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2023)
This study evaluates the maturity level of the Public Service Agency (BLU) at Jambi University (UNJA). The research uses descriptive analysis based on the BLU Maturity Rating worksheet to assess various aspects, including financial management, service quality, internal capabilities, governance, innovation, and environmental impact. The findings reveal that UNJA's BLU has achieved an overall maturity level 3.71. Internal capabilities scored the highest at level 5, while environmental aspects lagged at level 3. Recommendations are provided to enhance business ethics, risk management, and resource usage, improving the institution's maturity level and overall performance. These improvements are crucial for achieving a higher maturity level, ensuring better service quality, and promoting sustainable development within the institution.